2022
DOI: 10.1111/jpi.12805
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic lighting schedules to facilitate circadian adaptation to shifted timing of sleep and wake

Abstract: Circadian adaptation to shifted sleep/wake schedules may be facilitated by optimizing the timing, intensity and spectral characteristics of light exposure, which is the principal time cue for mammalian circadian pacemaker, and possibly by strategically timing nonphotic time cues such as exercise. Therefore, circadian phase resetting by light and exercise was assessed in 44 healthy participants (22 females, mean age [±SD] 36.2 ± 9.2 years), who completed 8‐day inpatient experiments simulating night shiftwork, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 88 publications
0
7
0
Order By: Relevance
“…Another study found dynamic indoor lighting at the workplace during the daytime advances melatonin onset and peripheral heat loss in the evening, which can be beneficial for people with delayed circadian rhythms [ 135 ]. Further, dynamic lighting can be also beneficial for circadian adaptation to shifted sleep–wake schedules [ 136 ]. The respective roles of spectral and illuminance changes cannot be discriminated yet, in terms of the beneficial effects of dynamic light.…”
Section: Light’s Influence On Human Cognition Is Mediated Through Mel...mentioning
confidence: 99%
“…Another study found dynamic indoor lighting at the workplace during the daytime advances melatonin onset and peripheral heat loss in the evening, which can be beneficial for people with delayed circadian rhythms [ 135 ]. Further, dynamic lighting can be also beneficial for circadian adaptation to shifted sleep–wake schedules [ 136 ]. The respective roles of spectral and illuminance changes cannot be discriminated yet, in terms of the beneficial effects of dynamic light.…”
Section: Light’s Influence On Human Cognition Is Mediated Through Mel...mentioning
confidence: 99%
“…Circadian rhythms are periodic 24-h variations that control critical biological functions in living beings such as emotion, body temperature, or alertness [ 15 ]. These rhythms are not only a consequence of external conditions since many studies have reported that organisms possess endogenous self-sustained rhythms even in the absence of arousing stimuli [ 3 , 15 , 16 ]. The previous studies reveal the presence of an endogenous circadian rhythm that controls our bodies.…”
Section: From Human To Robot Biological Rhythmsmentioning
confidence: 99%
“…Since ages, those living beings with better adaptive capabilities have demonstrated more chances to survive and genetically evolve in new generations [ 1 ]. In the XVIII century, Jean Jacques d’Ortous de Mairan [ 2 ] discovered that one of the leading causes of living beings’ adaptation was biological rhythms, periodic variations in their internal state adapted to ambient conditions [ 3 ]. Recent findings [ 4 ] highlight that the suprachiasmatic nucleus (SCN) is the primary pacemaker in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Induction of phase advances of the circadian clock should include exposure to dim light/darkness in the evening of the circadian clock period because exposure to bright light in the evening induces a phase delay of the circadian clock. 210,211 The phase advances in the circadian clock promote synchrony between the circadian clock and scheduled sleep-wake cycles in astronauts during space flight (b). Here, endogenous melatonin would increase in astronauts at the beginning of the sleep episode (c), contributing to the onset of sleep episode adjustment to the scheduled sleep-wake cycle of the shuttle mission.…”
Section: Low Light Intensities In Spacecraft Affect the Phases Of The...mentioning
confidence: 99%
“…In particular, the combination of exposure to bright light (~3000 lux) and the administration of a pharmacological dose of melatonin (5 mg) was reported to induce a great phase advance of the human circadian clock on Earth, 209 and can be expected to induce phase advances in astronauts during space flight. Induction of phase advances of the circadian clock should include exposure to dim light/darkness in the evening of the circadian clock period because exposure to bright light in the evening induces a phase delay of the circadian clock 210,211 . The phase advances in the circadian clock promote synchrony between the circadian clock and scheduled sleep–wake cycles in astronauts during space flight (b).…”
Section: Effects Of Space Flight On Circadian Clock and Sleep Of Astr...mentioning
confidence: 99%